Effect of Implant Location on Palateless Complete Overdenture Retention: an In Vitro Study - Nesma El-Amier; Ehab Elsaih; Mona Gibreel; Hassan El-Motaiam (Stilus Optimus, 2018)
Objectives: The purpose of this in vitro study was to evaluate effect of implant location on initial retention values of palateless complete overdentures retained by four o-rings at different inter-implant distances. Material and Methods: Two standard acrylic models representing completely edentulous maxillary arches were used. Four single piece ball type implants were placed in each model. Models were divided into two groups according to the distance between anterior and posterior implants. Two canine implants with 32 mm inter-implant distance were placed in both models. In one model (G1), two posterior implants were placed in second premolar region away from canine implants by 14 mm on both sides, while in the other model (G2), the two posterior implants were placed in first molar region away from canine implants by 22 mm on both sides. Eighteen palateless complete overdentures were constructed for each model. Overdentures were retained by four o-rings. Initial axial (central), and para-axial (anterior, posterior, and lateral) retention values of overdentures were estimated and compared using a universal testing machine. Results: Independent t-test revealed that implant location has a significant role in palateless complete overdenture retention with a level of significance set at P < 0.05. Conclusions: For in vitro simulated palateless implant overdentures retained by four o-rings, increasing the inter-implant distance between anterior and posterior implants is favourable for a more retentive prosthesis.